The Use of the Three-Dimensional Printed Polyether Ether Ketone Implant in Secondary Craniosynostosis Revision. Issue 6 (28th June 2022) - Atamian, Elisa K.; Hazkour, Nissim; Palacios, Jose; Pessino, Kenneth; Raza, Syed A.; Schneider, Steven J.; Bastidas, Nicholas
Abstract : Background: Skull deformities may be seen in patients years after craniosynostosis correction. These deformities cause psychosocial distress in affected patients. In this series, the authors describe the use of patient specific polyether ether ketone (PEEK) implants for correction of skull deformities after cranial vault remodeling for craniosynostosis. Methods: A chart review was conducted for 3 revision procedures performed by 1 plastic surgeon in collaboration with 1 neurosurgeon, both affiliated with Northwell Health. Preoperative computed tomography scans were used to design three-dimensional (3D) printed PEEK implants manufactured by KLS Martin. Implants were used to correct frontal and orbital asymmetry and skull deformities in each patient. Outcomes were assessed at 1 week, 1 month, and 3 months post-operation. Results: Two males and 1 female, ages 13, 17, and 19, underwent revision cranioplasty or orbital rim reconstruction using a custom, single piece 3D printed PEEK implant. All 3 patients underwent cranial vault remodeling in infancy; 1 was treated for coronal craniosynostosis and 2 were treated for metopic craniosynostosis. Revision cranioplasty operative times were 90, 105, and 147 minutes, with estimated blood loss of 45 mL, 75 mL, and 150 mL, respectively. One patient went home on post op day 1 and 2 patients went home on post op day 2. All patients had an immediate improvement in structural integrity and cranial contour, and all patients were pleased with their aesthetic results. Conclusions: Custom 3D printed PEEK implants offer a single piece solution in revision cranioplasty surgery to correct skull deformities after cranial vault remodeling for craniosynostosis.